#### Answer

$x=\frac{-(a^2+b^2)}{(a-b)}$

#### Work Step by Step

Bring x to one side and factor out $(a-b)$.
$ax-bx=-a^2-b^2$
$x(a-b)=-a^2-b^2$
$x(a-b)=-(a^2+b^2)$
Solve for x.
$x=\frac{-(a^2+b^2)}{(a-b)}$

Published by
Pearson

ISBN 10:
0321671791

ISBN 13:
978-0-32167-179-0

$x=\frac{-(a^2+b^2)}{(a-b)}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.